1990
DOI: 10.1111/j.1365-2125.1990.tb03674.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of flosequinan on submaximal exercise in patients with chronic cardiac failure.

Abstract: 1. Twenty patients with moderate to severe chronic cardiac failure were entered into a double‐blind parallel group study comparing flosequinan 100 mg daily with matching placebo. 2. After at least three prior exercise tests, cardiopulmonary parameters were assessed at rest and during submaximal exercise before and after 2 and 8 weeks of active drug or placebo. 3. Resting minute ventilation and respiratory rate were reduced by flosequinan compared with placebo, but oxygen uptake was unchanged. 4. Comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The reasons for this discrepancy are unclear. However, Elborn et al [9,10] also demonstrated that the peak oxygen uptake increased only by 13% whereas an increase in anaerobic threshold (20%) was larger. Thus, the drug may preferentially improve the anaerobic threshold.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The reasons for this discrepancy are unclear. However, Elborn et al [9,10] also demonstrated that the peak oxygen uptake increased only by 13% whereas an increase in anaerobic threshold (20%) was larger. Thus, the drug may preferentially improve the anaerobic threshold.…”
Section: Discussionmentioning
confidence: 90%
“…1). In severe heart failure, Elborn et al [9,10] demonstrated significant improvements in these measurements after 8 weeks' administration of flosequinan, at 100mg daily, compared to placebo treatment in a similarily designed double-blind study. The difference between our results and theirs may be attributed to the difference in the severity of heart failure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation